Journal kept during the Crimean War - Fisher, George (1854)
Consists of the journal (125 pp.) kept by "Vety. Surgeon Geo. Fisher, 5th Dragn Guards who died at Varna Augt 24th 1854" and a typed transcription (27 pp.) of it. The entries document the troops' departure from Ireland aboard the P. & O. steamer HIMALAYA on May 28th, their arrival in Constantinople (Turkey) on June 10th and in Varna (Bulgaria) on June 12th, and describe their camps and activities. Included are detailed descriptions of the Horse Bazaar at Stamboul, conditions in the camps (French and Turkish soldiers, cholera), and surrounding environments.
Program in Hellenic Studies with the support of the Stanley J. Seeger Hellenic Fund.
Keywords: Great Britain. -- Army. -- Regiment of Dragoon Guards, 5th -- Officers -- Diaries; Himalaya (Ship); Crimean War, 1853-1856 -- Personal narratives, English; Military camps -- Bulgaria; War horses -- Turkey; Diaries -- 19th century; Diaries